Calcium signaling pathways mediating synaptic potentiation triggered by amyotrophic lateral sclerosis IgG in motor nerve terminals - Pagani, M.R. (2006)
Sporadic amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that affects particularly motoneurons. Several pieces of evidence suggested the involvement of autoimmune mechanisms mediated by antibodies in ALS. However, the significance of those antibodies in the disease and the underlying mechanisms are unknown. Here we showed that IgG purified from a group of sporadic ALS patients, but not familial ALS patients, specifically interact with the presynaptic membrane of motoneurons through an antigen-antibody interaction and modulated synaptic transmission. Immunoreactivity against nerve terminals showed strong correlation with synaptic modulation ability. In addition, several controls have ruled out the possibility for this synaptic modulation to be mediated through proteases or nonspecific effects. Effective IgG potentiated both spontaneous and asynchronous transmitter release. Application of pharmacological inhibitors suggested that activation of this increased release required a nonconstitutive Ca2+ influx through N-type (Ca v2.2) channels and phospholipase C activity and that activation of IP3 and ryanodine receptors were necessary to both activate and sustain the increased release. Consistent with the notion that ALS is heterogeneous disorder, our results reveal that, in ∼50% of ALS patients, motor nerve terminals constitutes a target for autoimmune response. Copyright © 2006 Society for Neuroscience.